The Effects of Amlodipine on Left Ventricular Mass and Diastolic Function in Concentric and Eccentric Left Ventricular Hypertrophy - (:unkn) unknown (My University, 1996)
BACKGROUND: The effects of the antihypertensive therapy with amlodipine (5-10 mg/day) on left ventricular mass and diastolic function were examined in 30 mild to moderate essential hypertensive patients who have left ventricular hypertrophy (LVH) and diastolic dysfunction. METHODS AND RESULTS: Each patient's left ventricular mass was measured, and left ventricular diastolic function was assessed by echocardiographic Doppler examination at entry, and at 3 and 6 months after the initiation of the treatment. Amlodipine reduced both blood pressure (from 164 +/- 14/104 +/- 6 mmHg to 134 +/- 9/83 +/- 4 mmHg) and left ventricular mass index (from 160 +/- 30 g/m(2) to 137 +/- 26 g/m(2)) significantly at 3 months and both parameters maintained at these levels for 6 months. When the patients were classified according to the type of the LVH, a significant regression in left ventricular mass index was seen only in the patients who had concentric LVH was a relative wall thickness >/=0.44 (n = 16), but not in the eccentric LVH group (n = 14), although both groups were not significantly different from each other regarding the basal hemodynamic parameters, baseline left ventricular mass index and the decrease in blood pressure in response to amlodipine treatment. The mitral inflow E/A ratio did not show any significant change in either group. CONCLUSIONS: Amlodipine produced significant regression in LVH only in the patients with concentric LVH, but not those with eccentric LVH, while it did not change the diastolic dysfunction. Therefore, the type of LVH seems to be an important feature in determining the effects of antihypertensive treatment on left ventricular mass index.